ROLE OF PAST BEHAVIOUR IN APPLICATION OF TPB IN PREDICTING ENERGY SAVING BEHAVIOUR: A REVIEW - Ayu Primasari Andini; Low Sheau-Ting (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The energy sector is the largest source of emissions and accounting for nearly 68% of the world’s greenhouse gas emissions. Where 36% of all global final energy use is generated from buildings. Currently, the topic of energy-saving behaviour is attracting the attention of researchers, how to encourage users towards energy-saving behaviour (ESB). Theory of Planned Behaviour (TPB) is empirically recognized as a model widely used in predicting social behaviour. However, the TPB has received much debate and criticism about the narrow sufficiency of the three original determinants: Attitudes, Subjective Norms and Perceived Behaviour Control. This article discusses empirical support by several authors who acknowledged other related factor that need to be considered in developing a theoretical framework by adding Past Behaviour in predicting the energy saving behaviour of users to improve the ESB. An extensive literature search was conducted on 100 published literature in year 2011-2021, to explore the significance of past behaviour as an additional psychological factor of ESB in a building context. Content analysis conducted based on previous research published in leading journals (e.g. Scopus and Web of Science). About 30% of previous studies have found Past Behaviour as a significant contributing predictor of ESB beside the TPB original determinants. This study will help to provide a better understanding about social psychological determinants of energy saving behaviour hence serve as a guide to the building operator and relevant agencies in shaping strategy to promote energy saving behaviour among the occupants.